Sistem Diagnosis Penyakit Hipokalemia menggunakan Gabungan Metode Forward Chaining dan Certainty Factor - Surya, Angga Pratama; Fauziah, Fauziah; Nurhayati, Nurhayati (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
Hypokalemia can be a serious problem in humans which results in paralysis and causes death. This is caused by sufferers who are late in analyzing the symptoms and diseases. To facilitate. To speed up the process of diagnosis of these symptoms, an expert system can be done. This study aims for an initial diagnosis based on the symptoms experienced. This expert system can be used as a tool in making decisions. This study uses the method Forward Chaining and Certainty Factor (CF) to overcome the uncertainty of hypokalemia. The results of this expert system can help early diagnose hypokalemia, so that the disease can be treated as early as possible so as not to cause the disease to get worse in the future.